Homosexuality on the small screen: television and gay identity in Britain - Buckle, Sebastian (IB Tauris, 2018)
Television provides a unique account of the development of a homosexual identity across the western world, emerging as it did when ideas around sex and sexuality were themselves only just beginning to be publicly discussed. From the very earliest surviving drama featuring homosexuality in 1959, Homosexuality on the Small Screen explores each decade's programming in turn, looking at homosexual themes, storylines, and characters, situating them historically, and relating them to the broader events in British history. By doing so it examines the interactions between the medium and the reality of gay lives, showing how television mirrored the changes taking place in British society. For those with a homosexual - or emerging homosexual - sexual orientation, they were seminal in early personal and social development. For heterosexual viewers, these images were equally important in exploring a sexual other which otherwise remained hidden from them. They included positive storylines which helped improve public ideas about homosexuality, but also stereotypical images which propagated negative attitudes in the public consciousness. Homosexuality on the Small Screen charts this fascinating journey and television's role in the construction of a gay identity.